"Being able to do whatever you wanna do as a woman is important:" a qualitative exploration of contraception as a frame of reference for HIV prevention with PrEP - Emma Chew Murphy; Antoinette Danvers; Andrés Ramírez Zamudio; Karina Avila; Meghan Proehl; Tatiana Gonzalez-Argoti; Joanne E. Mantell; Laurie J. Bauman; Siobhan M. Dolan (BMC, 2022)
Plain Language Summary PrEP (pre-exposure prophylaxis) is a medicine taken daily by people at risk of getting HIV from sex or injection drug use. Although PrEP is a safe and effective medication for women, the use of PrEP remains exceedingly low among cis-gender women at risk of HIV in the US. This study examines how experiences with contraception among women of color, who disproportionately bear the burden of HIV acquisition, shape their perceptions and preferences regarding PrEP. We interviewed 30 women who self-identified as Black or Latina at an academic medical center in the Bronx. Similar to oral contraception, women in this study conceptualized PrEP as a "daily pill" to support their reproductive health. This report details how women's experiences with contraception may serve as the foundation to re-contextualize conversations on PrEP within a sex-positive framework that prioritizes pleasure, safety, and autonomy as integral to sexual and reproductive wellness.